Spider mites, host plants and new records for Brazil (Acari: Tetranychidae) - Flechtmann, Carlos H. W. (Entomological Communications, 2020)
A list of new records of spider mites (Acari: Tetranychidae) for Brazil based on specimens deposited in the Acarological Collection of Departamento de Entomologia e Acarologia, ESALQ, Universidade de São Paulo (Piracicaba, São Paulo, Brazil) is presented. The specimens studied were sent for identification and/or collected by us from different states of the country. The list includes 15 species belonging to seven different genera: Allonychus, Aponychus, Eutetranychus, Mononychellus, Schizotetranychus, Oligonychus and Tetranychus.